STUDY ON CONSTRUCTION OF PURSE SEINE IN SIBOLGA FISHING PORT PONDOK BATU DISTRICT NORTH SUMATRA - Silitonga, Candra; Syofyan, Irwandy; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on 09-23 May 2016 is located in Sibolga Fishing Port. The purpose of this study to know on type and purse seine construction for sized vessels 30 GT. The method used was survey and observation. Observed object is purse seine used on vessels 30 GT. Data collection was performed by means of measurements on sample. It known that purse seine for sized vessels 30 GT in Sibolga Fishing Port include into purse seine American type, it known from the construction that shaped four rectangular. The characteristic of purse seine is part of that bag (muih 1) is located on the edge of the webbing, and only be operated by one vessel.Keywords: Construction of Fishing Gear, Purse seine, Sibolga Fishing Port